Rice-husk-derived mesoporous 0D/2D C3N4 isotype heterojunction with improved quantum effect for photodegradation of tetracycline antibiotics. Issue 2 (1st February 2019) - Wang, Wei; Fang, Jiaojiao; Chen, Hu; Bao, Ningzhong; Lu, Chunhua
Abstract: Synthesis of highly active carbon nitride (C3 N4 )-based photocatalysts with specific structures for antibiotics degradation is a hot research topic in the photocatalysis field. In this study, rice-husk-derived SiO2 is employed as the sacrificial template to synthesize mesoporous photocatalyst with 0D/2D C3 N4 isotype heterojunction and improved quantum effect for tetracycline photodegradation. The structures and properties of as-prepared samples are systematically characterized and discussed. Results show that vacuum-assisted ultrasonic treatment is essential for the synthesis of the most active photocatalyst which is consisted of zero dimensional (0D) C3 N4 quantum dots adsorbed on the two dimensional (2D) C3 N4 sheets. The 0D/2D C3 N4 isotype heterojunction combines with the mesoporous structure is effective for transferring the photogenerated electrons and leaving the holes (h + ), which have higher oxidation potential because of the extended band gap, for effective tetracycline photodegradation under the visible light irradiation.